Resistance of cowpea (Vigna unguiculata (L.) Walp.) breeding lines to blackeye cowpea mosaic and cowpea aphid borne mosaic potyvirus isolates under experimental conditions - Boxtel, Jos van; Singh, B.; Thottappilly, G.; Maule, A. (2000)
Virus diseases cause substantial yield reduction in cowpea ( Vigna unguiculata (L.) Walp) production in West and Central Africa. Improved cowpea cultivars have been developed and distributed to various national programs but these cultivars were tested only against local virus isolates. To identify resistance applicable to a wider cowpea distribution, fourteen cowpea lines were analyzed under glasshouse conditions for susceptibility to infection by three isolates of Blackeye cowpea mosaic virus (BCMV-B1C) and ten isolates of Cowpea aphid-borne mosaic virus (CAbMV). The potyvirus isolates were representative of diverse geographical origins. The cowpea lines, derived from a Nigerian breeding program, comprised ten elite lines, three progenitor lines and one improved local cultivar. The elite lines differed widely in their susceptibility and did not always show a correlation between field performance and resistance to virus infection under experimental conditions. The two cowpea lines displaying highest overall resistance under experimental conditions were still susceptible to several CAbMV isolates. In most cases, it should be possible to complement these resistance deficiencies from genes in other lines. For the CAbMV-Morocco isolate, for which no resistance was identified, the development of engineered virus resistance may be appropriate. In general, the work argues for a combined approach in assessing new cowpea lines for disease resistance, where plants are challenged under both field and experimental conditions.